Ethnocultural Development of Future Music Teachers in Process of the Tatar Piano Music’s Studying - Salikhova, Liliya I.; Batyrshina, Gulnara I.; Safiullina, Liliya G.; Abdirakhman, Gulnar B. (Journal of History Culture and Art Research, 2017)
Studying the Tatar piano repertoire as element of national musical traditions is an important factor of ethnocultural development of the future music teachers of Tatarstan in the course of vocational training in higher education institution. It is caused inexhaustible by opportunities of ethnomusical heritage in formation of the personality, need of development in students of professionally significant ethnopsychological qualities, readiness for the solution of musical and educational tasks on the basis of the Tatar national culture. Disclosure of potential of the Tatar piano music in ethnocultural development of future music teachers became a research objective. On the basis of synthesis of experience of musical and performing training of future music teachers - students of Leo Tolstoy Institute of Philology and Intercultural Communication of Kazan Federal University, the performing analysis of the Tatar piano music, authors submit compositions in which found the brightest embodiment of tradition of the Tatar folk art. It is shown that, working on piano works, students learn deep moral and esthetic meaning of the Tatar folklore. They develop ethnocultural ideas of love, family values, gratitude to parents and respect of seniors, devotion to traditions of a sort, the importance of family education. Performance of songs always opened the emotional world of the person, reflected his intimate thoughts and experiences connected with hard destiny, aspiration fortunately and belief in the best. The deep moral and esthetic meaning of the Tatar folklore embodied by means of expression of piano music is shown in article; musical contents of works of the Tatar composers, their variety and opportunities in ethnocultural development of future music teachers reveal.